THE CHANGE IN PERCEPTION OF SUBMITTING CHILDREN TO CHILD WELFARE INSTITUTIONS IN DENPASAR CITY IN THE PERIOD 2006-2014 - Westerlaken, Rodney; Ardika, I Wayan; Ardhana, I Ketut; Darma Putra, I Nyoman (E-Journal of Cultural Studies, 2019)
Terroristic events, like the Bali bombings in 2002 and 2005, have major effects on a society. Prior research towards those effects have focused on the financial, economic and social economic effects, however this study focuses on the social cultural effect in the aftermath of the terroristic effects. The changed social cultural perception of submitting children to a Child Welfare Institution in the period 2006 to 2014 in Denpasar city, Bali. Sub questions to this problem statement what the reasons are that children are living in Child Welfare Institutions in Denpasar city recently and whether it is possible to connect social cultural perceptions of submitting children to Child Welfare Institutions in Denpasar city to coping mechanisms of the society after the terroristic attacks in 2002 and 2005. This research has used a quantitative approach, interviewing 50 children and 23 parents / familial caretakers. The outcomes have been analysed with help of the computer assisted qualitative data analysis software NVIVO. Research indicates that the trend of submitting children to Child Welfare Institutions, as a coping mechanism, in the first years after the second Bali bombing instigated a change in the social cultural system on Bali. The Balinese kinship system partly fell apart as a result of the Bali bombings, the keluarga besar is less considered to be asked for help and submitting a child to a Child Welfare Institution became an easy solution that currently continues to exist. It is concluded that the ethos, the moral formation as described by Foucault, is victimized by the failing system of aletheia and politeia, but that also ethos itself is victimized by contemporary forms of normalization. Keywords: social cultural change, terroristic attack, coping mechanism, Child Welfare Institutions.